2019
DOI: 10.4236/ojas.2019.93024
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Enteric Methane Emission in a Commercial Dairy Farm by a Novel Feed Supplement

Abstract: Several in vitro fermentation studies had demonstrated the efficacy of Mootral, a patent-pending natural feed supplement, in reducing methane gas production. In order to test the supplement's application in a commercial farm, Jersey (n = 121) and Holstein-Friesian (HF, n = 275) lactating cows received 500 g of pellets containing 3% Mootral powder for 12 weeks. Their enteric methane gas production was monitored using a hand-held laser methane detector. During 7 weeks of pre-Mootral supplementation period, dry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
0
20
1
Order By: Relevance
“…Adverse effects on DMI, ADG and feed efficiency were not detected over the 12-week trial. Lactating cattle offered Mootral incorporated in pellets at a rate of 0.640 g/kg DM for Holstein-Friesian and 1.21 g/kg DM for Jersey herd experienced suppression of CH 4 of 20.7% and 38.3% respectively (Vrancken et al 2019). Additionally, 3-5% increase in milk yield across breeds was observed with increased feed efficiency in the Jersey cattle.…”
Section: Essential Oil Blendsmentioning
confidence: 94%
See 1 more Smart Citation
“…Adverse effects on DMI, ADG and feed efficiency were not detected over the 12-week trial. Lactating cattle offered Mootral incorporated in pellets at a rate of 0.640 g/kg DM for Holstein-Friesian and 1.21 g/kg DM for Jersey herd experienced suppression of CH 4 of 20.7% and 38.3% respectively (Vrancken et al 2019). Additionally, 3-5% increase in milk yield across breeds was observed with increased feed efficiency in the Jersey cattle.…”
Section: Essential Oil Blendsmentioning
confidence: 94%
“…Mootral Ó is synthesised from natural products including garlic-and flavonoid-containing citrus extract and has demonstrated anti-methanogenic properties (Eger et al 2018;Roque et al 2019c;Vrancken et al 2019). The garlic component in Mootral Ó targets methanogenic archaea populations and protozoal communities in the rumen and has led to nearly complete inhibition of CH 4 production in vitro at a dosage of 2 g experimental mixture/day, without compromising bacterial population (Eger et al 2018).…”
Section: Essential Oil Blendsmentioning
confidence: 99%
“…However, the CH 4 emissions per kg of DMI of the beef steers were lower than those of the calves in the present study, indicating that the production of veal is possibly more emission-intensive than beef production. In lactating dairy cows, Mootral also showed a significant reduction in CH 4 emissions of up to 38% on a commercial farm [7]. Similarly, the effect of Mootral on CH 4 reduction by alteration of the rumen microbiome, particularly the archaeal community, was confirmed by using the in vitro RUSITEC technique with rumen fluid from Holstein cows without any negative impact on ru-Open Journal of Animal Sciences men fermentation [6].…”
Section: Discussionmentioning
confidence: 74%
“…Eger et al (2018) showed that Mootral reduced the percentage of methanogens during in vitro fermentation, which could be linked to a reduction of enteric CH 4 release and production rate [6]. In addition, Mootral demonstrated a reduction in enteric CH 4 production in lactating cows while increasing milk yield without affecting milk quality in commercial farm conditions [7]. Correspondingly, Mootral has exhibited a reduction in enteric CH 4 yield in beef cattle [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation